THE IMPORTANCE OF CERTAIN MORPHOLOGICAL CHARACTERISTICS IN WIND - SURFING TRAINING - Goran Oreb; Danijela Kostanić; Ivan Oreb (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The aim of the paper was to determine the relation between the morphological characteristics and the successfulness in wind - surfing training. The study was made on the sample of 53 female students from the Faculty of Kinesiology in Zagreb. The sample of variables for morphological characteristics assessment was defined by four anthro- pometric measures. The efficiency of performing wind - surfing elements was evaluated by three experts on the scale from 1 to 5. The results of the study showed a statistically significant correlation between body weight (TT) and two exam elements: turn down the wind (ONV) and turn to the wind (OUW).